Penerapan Pemilihan Media Pembelajaran - Zainul Abidin (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2016)
The process of selecting instructional media is basically one of the learning technology applications. In the initial activity, the selection must be carefully planned and determined, and specially designed to solve the learning problem at hand. The application of the selection of learning media which is carried out carefully and then used and utilized properly, will in turn improve the quality of learning.